The Improvement Of Learning To Write Through Cooperative Learning In Elementary School - Yulialistuti Yulialistuti (Universitas Tanjungpura, 2022)
The general research objective in this study is to improve learning to write through cooperative learning in grade 1 students at the 18 West Pontaiank SDN. With this research, it is hoped that students will be able and increase their knowledge during the learning process. This research method used descriptive research with a classroom action research (CAR) approach. The subjects in this study were first grade students at SDN 18 West Pontianak, totaling 24 students. During the learning, the students were still in a state of lack of understanding of increasing knowledge wherein the pre-cycle of 24 students only 10 students passed with a percentage of 41%, continued to cycle I, 17 students passed with a percentage of 70% and continued in cycle II with improved planning and implementation accurately and on target using the cooperative learning model, it could be said that 23 students passed from 24 students with a percentage of 95 %, with the Cooperative Learning model, the learning process is easier to follow by the students because there are smaller and more effective groupings if there are difficulties for students during learning.